Effect of synthesis temperature on optical performance of ZnO-TA nanostructures for optoelectronic applications - Aqilah, Kamaruzaman; Nurul Akmal, Che Lah (Sumy State University, 2026)
This study aims a comprehensive investigation into the synthesis and optical characterization of ZnO–TA nanostructures prepared via a low temperature hydrothermal green method under controlled pH conditions. The influence of synthesis temperature was systematically examined, showing clear effects on morphology, crystallinity, and optical behavior. Structural analysis confirmed nanorods with diameters below 100 nm, while temperature variation governed aggregation and aspect ratio differences due to rapid nucleation, elevated surface energy, and incomplete crystallization. Optical and photoluminescence studies revealed that intermediate synthesis conditions produced superior transparency, favorable band gap characteristics, and balanced defect emission compared to extreme temperatures. Collectively, these results identify 70C as the optimum synthesis temperature with nearly excellence transparency transparency, as evidenced by transmittance reaching 79% , combined with a favorable direct band gap offering ZnO–TA nanostructures with enhanced optical performance and positioning them as promising candidates for optoelectronic applications such as photodetectors and light emitting device.